Stabilizers, perovskite precursor solutions, perovskite solar cells and methods of making the same, perovskite tandem solar cells, photovoltaic modules
Patent Information
- Application Number
- CN202610542173.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-04-23
AI Technical Summary
[0005]本申请实施例提供一种稳定剂、钙钛矿前驱体溶液、钙钛矿太阳能电池及其制备方法、钙钛矿叠层太阳能电池、光伏组件,以解决或缓解上面提出的钙钛矿前驱体溶液的稳定性不足,降低钙钛矿太阳能电池的性能的技术问题
本申请实施例提供的稳定剂所含包括A-R-B化合物;该A-R-B化合物所含的A所示硫醚基、巯基或硫代羧基中的至少一种可作为主配位点与Pb²+形成强配位键,提升配位能力,该A-R-B化合物所含的B所示磺酸基、羧基或氨基甲酸基中的至少一种能够作为辅助配位点又可作为质子源,同步解决了阳离子去质子化与碘离子氧化两个关键降解路径,实现了单分子双功能稳定的作用,提高配位能力和稳定性,可以显著提升钙钛矿前驱体溶液的稳定性。
Smart Images

Figure CN122094392B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cell technology, and in particular to stabilizers, perovskite precursor solutions, perovskite solar cells and their preparation methods, perovskite tandem solar cells, and photovoltaic modules. Background Technology
[0002] Perovskite solar cells, with their excellent photovoltaic performance, have become one of the most promising photovoltaic technologies. The fabrication process of perovskite solar cells typically employs a solution-based method, which involves first preparing a perovskite precursor solution, then using methods such as spin coating, blade coating, or spray coating to prepare a perovskite thin film, ultimately resulting in the perovskite solar cell.
[0003] However, due to the unique properties of the perovskite precursor in the perovskite precursor solution, organic cation deprotonation reactions easily occur in the perovskite precursor solution system, accompanied by iodide ion oxidation reactions. This directly leads to aging and deterioration of the perovskite precursor solution, severely shortening its shelf life and effective usage time. Current solutions to this problem include using perovskite precursor solutions containing iodine bromide. Iodine bromide can effectively inhibit the conversion of primary amine ions to secondary amine ions in the perovskite precursor solution system, reducing deprotonation. However, iodine bromide alone and Pb²⁺… + Limited coordination ability prevents the simultaneous suppression of cation deprotonation and iodide oxidation processes in the perovskite precursor solution, resulting in insufficient stability of the perovskite precursor solution and reduced performance of perovskite solar cells.
[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the Invention
[0005] This application provides a stabilizer, a perovskite precursor solution, a perovskite solar cell and its preparation method, a perovskite tandem solar cell, and a photovoltaic module to solve or alleviate the technical problem mentioned above of insufficient stability of the perovskite precursor solution, which reduces the performance of the perovskite solar cell.
[0006] The first aspect of this application provides a stabilizer, the stabilizer comprising a compound with the general formula ARB; Wherein, R includes at least one of alkyl carbon chains, aryl carbon chains, and heteroatom-containing carbon chains; A includes at least one of thioether groups, mercapto groups, and thiocarboxyl groups; and B includes at least one of sulfonic acid groups, carboxyl groups, and carbamate groups.
[0007] The stabilizer provided in this application includes an ARB compound; at least one of the thioether group, mercapto group, or thiocarboxyl group shown in A of the ARB compound can serve as a major coordinating site with Pb². + By forming strong coordination bonds and enhancing coordination ability, at least one of the sulfonic acid group, carboxyl group or carbamate group represented by B in this ARB compound can serve as an auxiliary coordination site and a proton source, simultaneously solving the two key degradation pathways of cation deprotonation and iodide ion oxidation, achieving a single-molecule bifunctional stabilizing effect, improving coordination ability and stability, and significantly enhancing the stability of perovskite precursor solutions.
[0008] In the embodiments of this application, R includes at least one of alkyl carbon chains, aryl carbon chains, and heteroatom-containing carbon chains, which allows the stabilizer to react simultaneously with Pb². + It forms a stable chelate structure, enhances multiple coordination effects, and increases the thermal stability of the stabilizer, preventing decomposition or volatilization of the perovskite film during annealing, and ensuring that the stabilizer remains in the perovskite layer in a coordinated state to continue to play its role.
[0009] Optionally, the alkyl carbon chain includes a C2-C6 carbon chain.
[0010] In the embodiments of this application, the alkyl carbon chain includes a C2-C6 carbon chain, which can make the stabilizer react with Pb². + This forms a stable chelate structure and a chelate ring, improving coordination stability. In particular, the moderate length of the C2-C6 alkyl carbon chain maintains a reasonable spatial spacing, allowing the thioether, mercapto, or thiocarboxyl groups to act as the main coordination sites and smoothly bind to Pb²⁺. + Forming strong coordination bonds allows sulfonic acid, carboxyl, or carbamate groups to act as auxiliary coordination sites, fully leveraging the proton source effect to suppress cation deprotonation. However, if the carbon chain is too short, the steric hindrance of functional groups A and B is too great, leading to mutual interference and preventing them from functioning independently. Conversely, if the carbon chain is too long, the excessive flexibility of the ARB compound can cause the functional groups A and B to interact with Pb²⁺. + The binding efficiency of the coordination sites is reduced.
[0011] Optionally, the stabilizer includes at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid.
[0012] This application employs a stabilizer to construct a thiol-carboxyl coordinating system, achieving a single-molecule bifunctional stabilizing effect. This simultaneously blocks two major degradation pathways in the perovskite precursor solution: cation deprotonation and iodide oxidation. The application uses at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid as the stabilizer, maintaining a reasonable spatial spacing that allows the thiol group to act as the main coordination site for Pb². +By forming strong coordination bonds and allowing the carboxyl group to act as an auxiliary coordination site, the proton source can be fully utilized to inhibit cation deprotonation, which can significantly improve the stability of perovskite precursor solutions. This allows perovskite precursor solutions to remain in normal working condition even after long-term storage, thus enhancing the long-term stability of perovskite precursor solutions.
[0013] A second aspect of this application provides a perovskite precursor solution including a stabilizer as described in the embodiments of this application.
[0014] A third aspect of this application provides a perovskite layer, which is formed by preparing a stabilizer or a perovskite precursor solution as described in the embodiments of this application.
[0015] The fourth aspect of this application provides a perovskite solar cell, comprising a first carrier functional layer, a perovskite layer, and a second carrier functional layer stacked sequentially.
[0016] Optionally, the perovskite solar cell includes a first carrier functional layer, a perovskite layer, a second carrier functional layer, a transparent conductive layer, and an electrode, which are stacked sequentially.
[0017] The perovskite layer in the perovskite solar cell provided in this application includes the stabilizer as described above or is prepared from the perovskite precursor solution as described above. This can make the perovskite layer structure more stable, reduce the occurrence of defects in the perovskite layer caused by the aging of the perovskite precursor solution, and reduce the problem of performance degradation of the perovskite solar cell exceeding 10% after the perovskite precursor solution is placed.
[0018] Optionally, the first carrier functional layer and the second carrier functional layer are each independently selected from either the hole transport layer or the electron transport layer, and the first carrier functional layer and the second carrier functional layer are different.
[0019] The interface between the perovskite layer and the first carrier functional layer provided in this application is better, reducing interface defects, optimizing the photoelectric transmission path, and further improving the photoelectric conversion efficiency of the perovskite solar cell device.
[0020] Optionally, the thickness of the perovskite layer is 400nm-800nm.
[0021] The fifth aspect of this application provides a perovskite tandem solar cell, which includes a silicon substrate cell and a perovskite solar cell as described in the embodiments of this application, arranged in sequence.
[0022] The sixth aspect of this application provides a method for fabricating a perovskite solar cell, comprising the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in the embodiments of this application is deposited on the surface of the first carrier functional layer to form a perovskite thin film, and then annealed to form a perovskite layer. A second carrier functional layer is formed on the perovskite layer; A transparent conductive layer is formed on the second carrier functional layer.
[0023] Optionally, the method for fabricating the perovskite solar cell includes the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in the embodiments of this application is deposited on the surface of the first carrier functional layer to form a perovskite thin film, and then annealed to form a perovskite layer. A second carrier functional layer is formed on the perovskite layer; A transparent conductive layer is formed on the second carrier functional layer; Electrodes are formed on the transparent conductive layer.
[0024] Optionally, the mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL.
[0025] The method for preparing perovskite solar cells provided in this application involves forming a film on the surface of the first carrier functional layer using a perovskite precursor solution with added stabilizer. The mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL. At least one of the thioether group, mercapto group, or thiocarboxyl group in the stabilizer can serve as a major coordination site for Pb²⁻. + By forming strong coordination bonds and enhancing coordination ability, and using at least one of the sulfonic acid, carboxyl, or carbamate groups as an auxiliary coordination site and a proton source, the deprotonation side reaction of organic cations in the perovskite precursor solution is suppressed, achieving single-molecule bifunctional stabilization. Through the construction of a synergistic coordination system, single-molecule bifunctional stabilization is achieved, simultaneously blocking the two major degradation pathways of cation deprotonation and iodide oxidation in the perovskite precursor solution. This significantly improves the stability of the perovskite precursor solution, allowing it to maintain normal usability even after long-term storage. This enhances the long-term stability of the perovskite precursor solution, preventing performance degradation of the perovskite layer due to aging of the perovskite precursor solution. It also improves the uniformity, stability, and photoelectric performance of the perovskite layer, further enhancing the photoelectric conversion efficiency and stability of perovskite solar cell devices and extending their lifespan.
[0026] The seventh aspect of this application provides a photovoltaic module, including a solar cell as described above or a solar cell prepared by the method described above.
[0027] The embodiments of this application employing the above-described technical solution may have the following advantages: The stabilizer provided in this application includes an ARB compound; at least one of the thioether group, mercapto group, or thiocarboxyl group shown in A of the ARB compound can serve as a major coordinating site with Pb². + By forming strong coordination bonds and enhancing coordination ability, at least one of the sulfonic acid group, carboxyl group or carbamate group represented by B in this ARB compound can serve as an auxiliary coordination site and a proton source, simultaneously solving the two key degradation pathways of cation deprotonation and iodide ion oxidation, achieving a single-molecule bifunctional stabilizing effect, improving coordination ability and stability, and significantly enhancing the stability of perovskite precursor solutions.
[0028] The perovskite layer in the perovskite solar cell provided in this application includes the stabilizer as described above or is prepared from the perovskite precursor solution as described above. This can make the perovskite layer structure more stable, reduce the occurrence of defects in the perovskite layer caused by the aging of the perovskite precursor solution, and reduce the problem of performance degradation of the perovskite solar cell exceeding 10% after the perovskite precursor solution is placed.
[0029] The method for preparing perovskite solar cells provided in this application involves forming a film on the surface of the first carrier functional layer using a perovskite precursor solution with added stabilizer. The mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL. At least one of the thioether group, mercapto group, or thiocarboxyl group in the stabilizer can serve as a major coordination site for Pb²⁻. + By forming strong coordination bonds and enhancing coordination ability, and using at least one of the sulfonic acid, carboxyl, or carbamate groups as an auxiliary coordination site and a proton source, the deprotonation side reaction of organic cations in the perovskite precursor solution is suppressed, achieving single-molecule bifunctional stabilization. Through the construction of a synergistic coordination system, single-molecule bifunctional stabilization is achieved, simultaneously blocking the two major degradation pathways of cation deprotonation and iodide oxidation in the perovskite precursor solution. This significantly improves the stability of the perovskite precursor solution, allowing it to maintain normal usability even after long-term storage. This enhances the long-term stability of the perovskite precursor solution, preventing performance degradation of the perovskite layer due to aging of the perovskite precursor solution. It also improves the uniformity, stability, and photoelectric performance of the perovskite layer, further enhancing the photoelectric conversion efficiency and stability of perovskite solar cell devices and extending their lifespan. Attached Figure Description
[0030] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0031] Figure 1 This is a schematic diagram of the structure of a solar cell provided in an embodiment of this application.
[0032] Figure 2 This is a schematic diagram of the structure of the silicon-based battery provided in the embodiments of this application.
[0033] Explanation of reference numerals in the attached figures: Figure 1 In the middle: silicon substrate 100, hole transport layer 110, perovskite layer 120, passivation layer 130, electron transport layer 140, sputtering protection layer 150, transparent conductive layer 160, electrode 170, antireflection layer 180.
[0034] Figure 2 In the middle: silicon substrate 100, back silver grid layer 10, back transparent conductive oxide layer 11, back n-type doped amorphous silicon (a-Si:H) layer 12, back intrinsic amorphous silicon (a-Si:H) layer 13, N-type crystalline silicon substrate 14, front intrinsic amorphous silicon (a-Si:H) layer 15, front p-type doped amorphous silicon (a-Si:H) layer 16, front transparent conductive oxide layer 17. Detailed Implementation
[0035] The embodiments of this application are described in detail below, examples of which are illustrated in the accompanying drawings. In the drawings, for clarity, the dimensions of layers, regions, and elements, as well as their relative dimensions, may be exaggerated. Throughout, the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the features of this application and its embodiments can be combined with each other.
[0036] It should be understood that when an element or layer is referred to as "on," "adjacent to," "connected to," or "coupled to" other elements or layers, it may be directly on, adjacent to, connected to, or coupled to other elements or layers, or there may be intervening elements or layers. Conversely, when an element is referred to as "directly on," "directly adjacent to," "directly connected to," or "directly coupled to" other elements or layers, there are no intervening elements or layers. It should be understood that although the terms first, second, third, etc., may be used to describe various elements, components, areas, layers, and / or portions, these elements, components, areas, layers, and / or portions should not be limited by these terms. These terms are only used to distinguish one element, component, area, layer, or portion from another element, component, area, layer, or portion. Therefore, without departing from the teachings of this application, the first element, component, area, layer, or portion discussed below may be referred to as a second element, component, area, layer, or portion. And the discussion of a second element, component, area, layer, or portion does not imply that the first element, component, area, layer, or portion necessarily exists in this application.
[0037] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "joining," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0038] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0039] This application involves numerical intervals (i.e., numerical ranges). Unless otherwise specified, the distribution of selectable numerical values within a numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0040] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0041] This application provides a stabilizer, which includes compounds with the general formula ARB; Wherein, R includes at least one of alkyl carbon chains, aryl carbon chains, and heteroatom-containing carbon chains; A includes at least one of thioether groups, mercapto groups, and thiocarboxyl groups; and B includes at least one of sulfonic acid groups, carboxyl groups, and carbamate groups.
[0042] The stabilizer provided in this application includes an ARB compound; at least one of the thioether group, mercapto group, or thiocarboxyl group shown in A of the ARB compound can serve as a major coordinating site with Pb². + By forming strong coordination bonds and enhancing coordination ability, at least one of the sulfonic acid group, carboxyl group or carbamate group represented by B in this ARB compound can serve as an auxiliary coordination site and a proton source, simultaneously solving the two key degradation pathways of cation deprotonation and iodide ion oxidation, achieving a single-molecule bifunctional stabilizing effect, improving coordination ability and stability, and significantly enhancing the stability of perovskite precursor solutions.
[0043] In the embodiments of this application, R includes at least one of alkyl carbon chains, aryl carbon chains, and heteroatom-containing carbon chains, which allows the stabilizer to react simultaneously with Pb². + It forms a stable chelate structure, enhances multiple coordination effects, and increases the thermal stability of the stabilizer, preventing decomposition or volatilization of the perovskite film during annealing, and ensuring that the stabilizer remains in the perovskite layer in a coordinated state to continue to play its role.
[0044] In an optional embodiment, the alkyl carbon chain comprises a C2-C6 carbon chain.
[0045] In the embodiments of this application, the alkyl carbon chain includes a C2-C6 carbon chain, which can make the stabilizer react with Pb². + This forms a stable chelate structure and a chelate ring, improving coordination stability. In particular, the moderate length of the C2-C6 alkyl carbon chain maintains a reasonable spatial spacing, allowing the thioether, mercapto, or thiocarboxyl groups to act as the main coordination sites and smoothly bind to Pb²⁺. + Forming strong coordination bonds allows sulfonic acid, carboxyl, or carbamate groups to act as auxiliary coordination sites, fully leveraging the proton source effect to suppress cation deprotonation. However, if the carbon chain is too short, the steric hindrance of functional groups A and B is too great, leading to mutual interference and preventing them from functioning independently. Conversely, if the carbon chain is too long, the excessive flexibility of the ARB compound can cause the functional groups A and B to interact with Pb²⁺. + The binding efficiency of the coordination sites is reduced.
[0046] In an optional embodiment, the stabilizer includes at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid.
[0047] This application employs a stabilizer to construct a thiol-carboxyl coordinating system, achieving a single-molecule bifunctional stabilizing effect. This simultaneously blocks two major degradation pathways in the perovskite precursor solution: cation deprotonation and iodide oxidation. The application uses at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid as the stabilizer, maintaining a reasonable spatial spacing that allows the thiol group to act as the main coordination site for Pb². + By forming strong coordination bonds and allowing the carboxyl group to act as an auxiliary coordination site, the proton source can be fully utilized to inhibit cation deprotonation, which can significantly improve the stability of perovskite precursor solutions. This allows perovskite precursor solutions to remain in normal working condition even after long-term storage, thus enhancing the long-term stability of perovskite precursor solutions.
[0048] The stabilizers used in this application include at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid. By constructing a thiol-carboxyl synergistic coordination system through the stabilizer, a single-molecule bifunctional stabilizing effect is achieved. This simultaneously blocks the two major degradation pathways of cation deprotonation and iodide ion oxidation in the perovskite precursor solution, which can significantly improve the stability of the perovskite precursor solution. This allows the perovskite precursor solution to maintain a normal usable state even after long-term storage, thus improving the long-term stability of the perovskite precursor solution.
[0049] This application provides a perovskite precursor solution including the stabilizer described in the above application embodiments.
[0050] The perovskite precursor solution provided in this application embodiment contains the stabilizer described in the above application embodiment. At least one of the thioether group, mercapto group, or thiocarboxyl group in the stabilizer can serve as the main coordination site for Pb². + By forming strong coordination bonds and enhancing coordination ability, and using at least one of the sulfonic acid group, carboxyl group, or carbamate group as an auxiliary coordination site and a proton source, the deprotonation side reaction of organic cations in the perovskite precursor solution is inhibited, thus achieving a single-molecule bifunctional stabilization effect. By constructing a synergistic coordination system, a single-molecule bifunctional stabilization effect is achieved, simultaneously blocking the two major degradation pathways of cation deprotonation and iodide ion oxidation in the perovskite precursor solution. This can significantly improve the stability of the perovskite precursor solution, allowing it to maintain normal usability even after long-term storage, thus enhancing the long-term stability of the perovskite precursor solution.
[0051] The mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL (exemplary values include 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2 mg / mL, 2.5 mg / mL, 2.8 mg / mL, 3 mg / mL, etc.).
[0052] The stabilizer provided in this application has a mass-volume concentration of 1 mg / mL-3 mg / mL in the perovskite precursor solution, which can significantly improve the stability of the perovskite precursor solution. This allows the perovskite precursor solution to maintain normal usability even after long-term storage, thus improving its long-term stability. However, when the mass-volume concentration of the stabilizer in the perovskite precursor solution is too low, it cannot effectively prevent the performance degradation of the perovskite layer caused by the aging of the perovskite precursor solution, thereby reducing the photoelectric conversion efficiency of the perovskite solar cell. When the mass-volume concentration of the stabilizer in the perovskite precursor solution is too high, the stabilizer will aggregate, failing to effectively suppress the deprotonation side reaction of organic cations in the perovskite precursor solution, thus failing to effectively improve the stability of the perovskite precursor solution and consequently reducing the photoelectric conversion efficiency of the perovskite solar cell.
[0053] In an optional embodiment, the perovskite precursor solution comprises Cs at a molar concentration of 1-2 mol / L (exemplary concentrations include 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, etc.). 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3.
[0054] This application provides a perovskite layer, which is formed by preparing a stabilizer or a perovskite precursor solution as described in this application.
[0055] This application provides a perovskite solar cell, comprising a first carrier functional layer, a perovskite layer, and a second carrier functional layer stacked sequentially.
[0056] In an optional embodiment, the perovskite solar cell includes a first carrier functional layer, a perovskite layer, a second carrier functional layer, a transparent conductive layer, and an electrode, which are stacked sequentially.
[0057] The perovskite layer in the perovskite solar cell provided in this application includes the stabilizer as described above or is prepared from the perovskite precursor solution as described above. This can make the perovskite layer structure more stable, reduce the occurrence of defects in the perovskite layer caused by the aging of the perovskite precursor solution, and reduce the problem of performance degradation of the perovskite solar cell exceeding 10% after the perovskite precursor solution is placed.
[0058] In an optional embodiment, the first carrier functional layer and the second carrier functional layer are each independently selected from either a hole transport layer or an electron transport layer, and the first carrier functional layer and the second carrier functional layer are different; when the first carrier functional layer is a hole transport layer, the second carrier functional layer is an electron transport layer; when the first carrier functional layer is an electron transport layer, the second carrier functional layer is a hole transport layer.
[0059] The interface between the perovskite layer and the first carrier functional layer provided in this application is better, reducing interface defects, optimizing the photoelectric transmission path, and further improving the photoelectric conversion efficiency of the perovskite solar cell device.
[0060] In an optional embodiment, the thickness of the perovskite layer is 400nm-800nm (exemplary, such as 400nm, 500nm, 600nm, 700nm, 800nm, etc.).
[0061] This application provides a perovskite tandem solar cell, which includes a silicon substrate cell and a perovskite solar cell as described in this application embodiment, arranged in sequence.
[0062] In an optional embodiment, the perovskite tandem solar cell includes a silicon base cell, a first carrier functional layer, a perovskite layer, a second carrier functional layer, a transparent conductive layer, and an electrode, which are stacked sequentially.
[0063] In an optional embodiment, the perovskite tandem solar cell includes a silicon base cell, a first carrier functional layer, a perovskite layer, a passivation layer, a second carrier functional layer, a sputtering protection layer, a transparent conductive layer, an electrode, and an antireflection layer, which are stacked sequentially.
[0064] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in the embodiments of this application is deposited on the surface of the first carrier functional layer to form a perovskite thin film, and then annealed to form a perovskite layer. A second carrier functional layer is formed on the perovskite layer; A transparent conductive layer is formed on the second carrier functional layer.
[0065] The method for preparing the perovskite solar cell includes the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in the embodiments of this application is deposited on the surface of the first carrier functional layer to form a perovskite thin film, and then annealed to form a perovskite layer. A second carrier functional layer is formed on the perovskite layer; A transparent conductive layer is formed on the second carrier functional layer; Electrodes are formed on the transparent conductive layer.
[0066] In an optional embodiment, the mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL (exemplary values include 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2 mg / mL, 2.5 mg / mL, 2.8 mg / mL, 3 mg / mL, etc.).
[0067] The method for preparing perovskite solar cells provided in this application involves forming a film on the surface of the first carrier functional layer using a perovskite precursor solution with added stabilizer. The mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL. At least one of the thioether group, mercapto group, or thiocarboxyl group in the stabilizer can serve as a major coordination site for Pb²⁻. +By forming strong coordination bonds and enhancing coordination ability, and using at least one of the sulfonic acid, carboxyl, or carbamate groups as an auxiliary coordination site and a proton source, the deprotonation side reaction of organic cations in the perovskite precursor solution is suppressed, achieving single-molecule bifunctional stabilization. Through the construction of a synergistic coordination system, single-molecule bifunctional stabilization is achieved, simultaneously blocking the two major degradation pathways of cation deprotonation and iodide oxidation in the perovskite precursor solution. This significantly improves the stability of the perovskite precursor solution, allowing it to maintain normal usability even after long-term storage. This enhances the long-term stability of the perovskite precursor solution, preventing performance degradation of the perovskite layer due to aging of the perovskite precursor solution. It also improves the uniformity, stability, and photoelectric performance of the perovskite layer, further enhancing the photoelectric conversion efficiency and stability of perovskite solar cell devices and extending their lifespan.
[0068] In an optional embodiment, the method for fabricating the perovskite solar cell includes the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in the embodiments of this application is deposited on the surface of the first carrier functional layer to form a perovskite thin film, and then annealed to form a perovskite layer. A passivation layer is formed on the perovskite layer; A second carrier functional layer is formed on the passivation layer; A sputtering protective layer is formed on the second carrier functional layer; A transparent conductive layer is formed on the sputtering protective layer; Electrodes are formed on the transparent conductive layer; An antireflection layer is formed on the electrode.
[0069] The perovskite solar cell fabrication method provided in this application uses a perovskite precursor solution with added stabilizer to form a film on the surface of the first carrier functional layer. This avoids the performance degradation of the perovskite layer caused by the aging of the perovskite precursor solution, improves the uniformity, stability and photoelectric performance of the perovskite layer, further improves the photoelectric conversion efficiency and stability of the perovskite solar cell device, and extends its service life.
[0070] In an optional embodiment, the method for fabricating the perovskite solar cell includes the following steps: Nickel oxide is deposited on a silicon substrate to form a hole transport layer with a thickness of 10nm-15nm (exemplary, such as 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, etc.); Cs at molar concentrations of 1-2 mol / L (exemplary concentrations include 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, etc.) 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 Add the stabilizer described above to the perovskite precursor solution to form perovskite precursor solution a, wherein the mass-volume concentration of the stabilizer in perovskite precursor solution a is 1 mg / mL-3 mg / mL; after the perovskite precursor solution a is left to stand for 1-20 days (exemplary, such as 1 day, 5 days, 10 days, 20 days, etc.), the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation; a perovskite thin film is formed, and an annealing treatment is performed to form a thickness of 400- A perovskite layer of 1000 nm (exemplary, such as 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc.); the perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of N,N-dimethylformamide (DMF) to dimethyl sulfoxide (DMSO) is (3-5):1 (exemplary, such as 3:1, 4:1, 5:1, etc.); Phenethyl ammonium iodide is deposited on the perovskite layer to form a passivation layer with a thickness of 1-5 nm (exemplary, such as 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc.); Fullerenes are deposited on the passivation layer using a thermal evaporation method to form an electron transport layer with a thickness of 20-40 nm (exemplary, such as 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, etc.). Tin dioxide is deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer with a thickness of 10-30 nm (exemplary, such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, etc.). IZO is sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer with a thickness of 50-90nm (exemplary, such as 50nm, 60nm, 70nm, 80nm, 90nm, etc.). Silver is deposited on the antireflection layer by thermal evaporation to form an electrode with a thickness of 200-600 nm (exemplary thicknesses include 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, etc.); Magnesium fluoride is deposited on a transparent conductive layer using a thermal evaporation method to form an antireflection layer with a thickness of 80-120 nm (exemplary thicknesses include 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, etc.).
[0071] like Figure 2 As shown, the silicon-based solar cell includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0072] The preparation method of each layer in the silicon bottom battery in this application embodiment is not limited. Conventional preparation methods (such as chemical vapor deposition, physical vapor deposition, etc.) can be used to form the above layer structure.
[0073] In an optional embodiment, the method for fabricating the silicon-based solar cell includes: Amorphous silicon (a-Si:H) is deposited on the first and second surfaces of an N-type crystalline silicon substrate 14 at a chemical vapor deposition (CVD) temperature of 180-210°C (exemplary values such as 180°C, 190°C, 200°C, 205°C, 210°C, etc.) to obtain a front intrinsic amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13. Amorphous silicon (a-Si:H) is deposited on the surface of the intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of -210℃ (exemplary, such as 180℃, 190℃, 200℃, 205℃, 210℃, etc.) to obtain a p-type doped amorphous silicon (a-Si:H) layer 16 on the front side; an amorphous silicon (a-Si:H) layer 16 is obtained by depositing amorphous silicon (a-Si:H) on the front side at a deposition temperature of 180-210℃ (exemplary, such as 180℃, 190℃, 200℃, 205℃, 210℃, etc.). Amorphous silicon (a-Si:H) is deposited on the surface of the intrinsic amorphous silicon (a-Si:H) layer 13 on the back side at a deposition temperature of 0℃ (e.g., 0℃) to obtain the n-type doped amorphous silicon (a-Si:H) layer 12 on the back side. ITO (indium tin oxide) is deposited on the surface of the n-type doped amorphous silicon (a-Si:H) layer 12 on the back side and the p-type doped amorphous silicon (a-Si:H) layer 16 on the front side using physical vapor deposition at a deposition temperature of 70-90℃ (e.g., 70℃, 75℃, 80℃, 85℃, 90℃) to obtain the transparent conductive oxide layer 11 on the back side and the transparent conductive oxide layer 17 on the front side, respectively. Ag is deposited on the surface of the transparent conductive oxide (TCO) layer 11 on the back side using physical vapor deposition at a deposition temperature of 80-110℃ (e.g., 80℃, 85℃, 90℃, 100℃, 105℃, 110℃) to obtain the silver gate layer 10 on the back side.
[0074] In an optional embodiment, the thickness of the back silver grid layer 10 is 10-20 μm (exemplary, such as 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, etc.).
[0075] In an optional embodiment, the thickness of the back transparent conductive oxide layer 11 is 80-100 nm (exemplary, such as 80 nm, 90 nm, 100 nm, etc.).
[0076] In an optional embodiment, the thickness of the back n-type doped amorphous silicon (a-Si:H) layer 12 is 5-20 nm (exemplary, such as 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, etc.).
[0077] In an optional embodiment, the thickness of the back intrinsic amorphous silicon (a-Si:H) layer 13 is 2-10 nm (exemplary, such as 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.).
[0078] In an optional embodiment, the thickness of the N-type crystalline silicon substrate 14 is 100-200 μm (exemplary, such as 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, etc.).
[0079] In an optional embodiment, the thickness of the front intrinsic amorphous silicon (a-Si:H) layer 15 is 2-10 nm (exemplary, such as 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.).
[0080] In an optional embodiment, the thickness of the front p-type doped amorphous silicon (a-Si:H) layer 16 is 5-20 nm (exemplary, such as 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, etc.).
[0081] In an optional embodiment, the thickness of the front transparent conductive oxide layer 17 is 70-120 nm (exemplary, such as 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, etc.).
[0082] This application provides a photovoltaic module, including a perovskite solar cell as described above or a perovskite solar cell prepared by the method described above.
[0083] The following section will present performance tests on the structure or fabrication method of the perovskite solar cell provided in the embodiments of this application, as well as related comparative examples.
[0084] Group 1 Experiment The first set of experiments provides Examples 1-4; Examples 1-4 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid with a mass-volume concentration of 2 mg / mL was added to the perovskite precursor solution to form perovskite precursor solution a. The perovskite precursor solution a was placed for 1 day, 5 days, 10 days and 20 days respectively before perovskite solar cells were prepared.
[0085]
Example 1
[0086] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide is deposited on the silicon substrate 100 to form a hole transport layer 110 with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a was 2 mg / mL; after the perovskite precursor solution a was left to stand for 1 day, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film was formed, and a perovskite layer 120 with a thickness of 600 nm was formed by annealing at 120°C for 15 min; Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer 130 with a thickness of 2 nm; Fullerenes were deposited on the passivation modification layer by thermal evaporation to form an electron transport layer 140 with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer 150 with a thickness of 20 nm; IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer 160 with a thickness of 60 nm. Silver was deposited on a transparent conductive layer by thermal evaporation to form an electrode 170 with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer 180 with a thickness of 100 nm.
[0087] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0088] like Figure 2As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0089] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0090]
Example 2
[0091] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 2 mg / mL; after the perovskite precursor solution a is placed for 5 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0092] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0093]
Example 3
[0094] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 2 mg / mL; after the perovskite precursor solution a is placed for 10 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0095] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0096]
Example 4
[0097] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 2 mg / mL; after the perovskite precursor solution a is placed for 20 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0098] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0099] Second group of experiments The second set of experiments provides Examples 5-8; Examples 5-8 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid was added to the perovskite precursor solution to form perovskite precursor solution a. The mass-volume concentration of 3-mercaptopropionic acid in the perovskite precursor solution a was 1 mg / mL. The perovskite precursor solution a was left to stand for 1 day, 5 days, 10 days and 20 days respectively before perovskite solar cells were prepared.
[0100]
Example 5
[0101] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide was deposited on a silicon substrate to form a hole transport layer with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 1 mg / mL; after the perovskite precursor solution a is left to stand for 1 day, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film is formed, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment; Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer with a thickness of 2 nm; Fullerenes were deposited on the passivation layer using a thermal evaporation method to form an electron transport layer with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer with a thickness of 20 nm. IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer with a thickness of 60 nm. Silver was deposited on a transparent conductive layer using a thermal evaporation method to form an electrode with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer with a thickness of 100 nm.
[0102] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0103] like Figure 2 As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0104] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0105]
Example 6
[0106] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 1 mg / mL; after the perovskite precursor solution a is placed for 5 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film is formed, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0107] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0108]
Example 7
[0109] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 1 mg / mL; after the perovskite precursor solution a is placed for 10 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film is formed, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0110] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0111]
Example 8
[0112] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 1 mg / mL; after the perovskite precursor solution a is placed for 20 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation; a perovskite thin film is formed, and a perovskite layer with a thickness of 600 nm is formed by annealing.
[0113] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0114] Third group of experiments The third set of experiments provides Examples 9-12; Examples 9-12 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 4-Mercaptobutyric acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 4-mercaptobutyric acid in perovskite precursor solution a was 2 mg / mL; perovskite solar cells were prepared after the perovskite precursor solution a was left to stand for 1 day, 5 days, 10 days and 20 days respectively.
[0115]
Example 9
[0116] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide was deposited on a silicon substrate to form a hole transport layer with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.254-Mercaptobutyric acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 4-mercaptobutyric acid in perovskite precursor solution a was 2 mg / mL; after the perovskite precursor solution a was left to stand for 1 day, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing. Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer with a thickness of 2 nm; Fullerenes were deposited on the passivation layer using a thermal evaporation method to form an electron transport layer with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer with a thickness of 20 nm. IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer with a thickness of 60 nm. Silver was deposited on a transparent conductive layer using a thermal evaporation method to form an electrode with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer with a thickness of 100 nm.
[0117] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0118] like Figure 2 As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0119] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0120]
Example 10
[0121] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.254-Mercaptobutyric acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 4-mercaptobutyric acid in perovskite precursor solution a was 2 mg / mL; after the perovskite precursor solution a was placed for 5 days, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0122] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0123]
Example 11
[0124] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 4-Mercaptobutyric acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 4-mercaptobutyric acid in perovskite precursor solution a was 2 mg / mL; after the perovskite precursor solution a was placed for 10 days, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0125] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0126]
Example 12
[0127] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA0.15 FA 0.8 Pb(I 0.75 Br 0.25 4-Mercaptobutyric acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 4-mercaptobutyric acid in perovskite precursor solution a was 2 mg / mL; after the perovskite precursor solution a was placed for 20 days, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing treatment.
[0128] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0129] Fourth group of experiments The fourth group of experiments provides Examples 13-16; Examples 13-16 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-mercaptopropionic acid with a mass-volume concentration of 3 mg / mL was added to the perovskite precursor solution to form perovskite precursor solution a. The perovskite precursor solution a was left to stand for 1 day, 5 days, 10 days and 20 days respectively before perovskite solar cells were prepared.
[0130]
Example 13
[0131] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide is deposited on the silicon substrate 100 to form a hole transport layer 110 with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a was 3 mg / mL; after the perovskite precursor solution a was left to stand for 1 day, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer 120 with a thickness of 600 nm was formed by annealing at 120°C for 15 min; Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer 130 with a thickness of 2 nm; Fullerenes were deposited on the passivation modification layer by thermal evaporation to form an electron transport layer 140 with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer 150 with a thickness of 20 nm; IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer 160 with a thickness of 60 nm. Silver was deposited on a transparent conductive layer by thermal evaporation to form an electrode 170 with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer 180 with a thickness of 100 nm.
[0132] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0133] like Figure 2 As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0134] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0135]
Example 14
[0136] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 3 mg / mL; after the perovskite precursor solution a is placed for 5 days, it is placed on the surface of the hole transport layer for film formation to form a perovskite thin film, and then annealed to form a perovskite layer with a thickness of 600 nm.
[0137] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0138]
Example 15
[0139] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 3 mg / mL; after the perovskite precursor solution a is placed for 10 days, it is placed on the surface of the hole transport layer for film formation to form a perovskite thin film, and then annealed to form a perovskite layer with a thickness of 600 nm.
[0140] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0141]
Example 16
[0142] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 3 mg / mL; after the perovskite precursor solution a is placed for 20 days, it is placed on the surface of the hole transport layer for film formation to form a perovskite thin film, and then annealed to form a perovskite layer with a thickness of 600 nm.
[0143] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0144] Fifth group of experiments The fifth group of experiments provides Examples 17-20; Examples 17-20 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid with a mass-volume concentration of 0.5 mg / mL was added to the perovskite precursor solution to form perovskite precursor solution a. The perovskite precursor solution a was left to stand for 1 day, 5 days, 10 days and 20 days respectively before perovskite solar cells were prepared.
[0145]
Example 17
[0146] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide is deposited on the silicon substrate 100 to form a hole transport layer 110 with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a was 0.5 mg / mL; after the perovskite precursor solution a was left to stand for 1 day, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation treatment; a perovskite thin film was formed, and a perovskite layer 120 with a thickness of 600 nm was formed by annealing at 120°C for 15 min; Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer 130 with a thickness of 2 nm; Fullerenes were deposited on the passivation modification layer by thermal evaporation to form an electron transport layer 140 with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer 150 with a thickness of 20 nm; IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer 160 with a thickness of 60 nm. Silver was deposited on a transparent conductive layer by thermal evaporation to form an electrode 170 with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer 180 with a thickness of 100 nm.
[0147] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0148] like Figure 2 As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0149] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0150]
Example 18
[0151] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 0.5 mg / mL; after the perovskite precursor solution a is placed for 5 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0152] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0153]
Example 19
[0154] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 0.5 mg / mL; after the perovskite precursor solution a is placed for 10 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0155] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0156]
Example 20
[0157] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 0.5 mg / mL; after the perovskite precursor solution a is placed for 20 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0158] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0159] Sixth experiment The sixth group of experiments provides Examples 21-24; Examples 21-24 provide Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid with a mass-volume concentration of 4 mg / mL was added to the perovskite precursor solution to form perovskite precursor solution a. The perovskite precursor solution a was placed for 1 day, 5 days, 10 days and 20 days respectively before perovskite solar cells were prepared.
[0160]
Example 21
[0161] This application provides a method for fabricating a perovskite solar cell, comprising the following steps: Nickel oxide is deposited on the silicon substrate 100 to form a hole transport layer 110 with a thickness of 10 nm; To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid was added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a was 4 mg / mL; after the perovskite precursor solution a was left to stand for 1 day, the perovskite precursor solution a was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer 120 with a thickness of 600 nm was formed by annealing at 120°C for 15 min; Phenethyl ammonium iodide was deposited on the perovskite layer to form a passivation layer 130 with a thickness of 2 nm; Fullerenes were deposited on the passivation modification layer by thermal evaporation to form an electron transport layer 140 with a thickness of 25 nm. Tin dioxide was deposited on the electron transport layer using atomic layer deposition to form a sputtering protective layer 150 with a thickness of 20 nm; IZO was sputtered onto the sputtering protective layer using a sputtering instrument to form a transparent conductive layer 160 with a thickness of 60 nm. Silver was deposited on a transparent conductive layer by thermal evaporation to form an electrode 170 with a thickness of 400 nm. Magnesium fluoride was deposited on a metal electrode by thermal evaporation to form an antireflection layer 180 with a thickness of 100 nm.
[0162] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0163] like Figure 2 As shown, the silicon-based solar cell 100 includes, from bottom to top, a back silver grid layer 10, a back transparent conductive oxide layer 11, a back n-type doped amorphous silicon (a-Si:H) layer 12, a back intrinsic amorphous silicon (a-Si:H) layer 13, an N-type crystalline silicon substrate 14, a front intrinsic amorphous silicon (a-Si:H) layer 15, a front p-type doped amorphous silicon (a-Si:H) layer 16, and a front transparent conductive oxide layer 17.
[0164] The method for preparing the silicon-based solar cell includes: Amorphous silicon (a-Si:H) layer 15 and a back intrinsic amorphous silicon (a-Si:H) layer 13 are obtained by chemical vapor deposition (CVD) at a deposition temperature of 200°C on the first and second surfaces of an N-type crystalline silicon substrate 14. Amorphous silicon (a-Si:H) layer 16 is then deposited on the surface of the front intrinsic amorphous silicon (a-Si:H) layer 15 at a deposition temperature of 200°C. Finally, amorphous silicon (a-Si:H) layer 16 is deposited on the back intrinsic amorphous silicon (a-Si:H) layer 13 at a deposition temperature of 200°C. Amorphous silicon (a-Si:H) is deposited on the surface of the i:H layer 13 to obtain the back n-type doped amorphous silicon (a-Si:H) layer 12; ITO (indium tin oxide) is deposited on the surfaces of the back n-type doped amorphous silicon (a-Si:H) layer 12 and the front p-type doped amorphous silicon (a-Si:H) layer 16 at a deposition temperature of 80°C using physical vapor deposition to obtain the back transparent conductive oxide layer 11 and the front transparent conductive oxide layer 17, respectively; Ag is deposited on the surface of the back transparent conductive oxide (TCO) layer 11 at a deposition temperature of 100°C using physical vapor deposition to obtain the back silver gate layer 10. The back silver gate layer 10 has a thickness of 20 μm, the back transparent conductive oxide layer 11 has a thickness of 100 nm, the back n-type doped amorphous silicon (a-Si:H) layer 12 has a thickness of 10 nm, the back intrinsic amorphous silicon (a-Si:H) layer 13 has a thickness of 5 nm, the N-type crystalline silicon substrate 14 has a thickness of 120 μm, the front intrinsic amorphous silicon (a-Si:H) layer 15 has a thickness of 5 nm, the front p-type doped amorphous silicon (a-Si:H) layer 16 has a thickness of 10 nm, and the front transparent conductive oxide layer 17 has a thickness of 120 nm.
[0165]
Example 22
[0166] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.253-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 4 mg / mL; after the perovskite precursor solution a is placed for 5 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0167] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0168]
Example 23
[0169] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 4 mg / mL; after the perovskite precursor solution a is placed for 10 days, the perovskite precursor solution a is placed on the surface of the hole transport layer for film formation treatment to form a perovskite thin film, and a perovskite layer with a thickness of 600 nm is formed by annealing treatment.
[0170] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0171]
Example 24
[0172] The specific content is as follows: To Cs with a molar concentration of 1.7 mol / L 0.05 MA0.15 FA 0.8 Pb(I 0.75 Br 0.25 3-Mercaptopropionic acid is added to the perovskite precursor solution of 3 to form perovskite precursor solution a, wherein the mass-volume concentration of 3-mercaptopropionic acid in perovskite precursor solution a is 4 mg / mL; after the perovskite precursor solution a is placed for 20 days, it is placed on the surface of the hole transport layer for film formation to form a perovskite thin film, and then annealed to form a perovskite layer with a thickness of 600 nm.
[0173] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0174] Control group experiment The control group experiments provided Comparative Examples 1-4; Comparative Examples 1-4 provided Cs with a molar concentration of 1.7 mol / L. 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 The perovskite precursor solution was prepared by placing it for 1 day, 5 days, 10 days and 20 days respectively before preparing perovskite solar cells.
[0175] Comparative Example 1 The perovskite solar cell of Comparative Example 1 was prepared according to the preparation method of the perovskite solar cell provided in Example 1, except that 3-mercaptopropionic acid was not added to the perovskite precursor solution.
[0176] The specific content is as follows: Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 After the perovskite precursor solution of 3 was placed for 1 day, it was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0177] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0178] Comparative Example 2 Comparative Example 2 perovskite solar cells were prepared using the same method as Comparative Example 1, except that the perovskite precursor solution was left to stand for 5 days before being placed on the surface of the hole transport layer for film formation.
[0179] The specific content is as follows: Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 After the perovskite precursor solution of 3 was placed for 5 days, it was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0180] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0181] Comparative Example 3 The perovskite solar cell of Comparative Example 3 was prepared according to the preparation method of the perovskite solar cell provided in Comparative Example 1, except that the perovskite precursor solution was placed for 10 days and then placed on the surface of the hole transport layer for film formation.
[0182] The specific content is as follows: Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 After the perovskite precursor solution of 3 was placed for 10 days, it was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0183] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0184] Comparative Example 4 The perovskite solar cell of Comparative Example 4 was prepared according to the preparation method of the perovskite solar cell provided in Comparative Example 1, except that the perovskite precursor solution was placed for 20 days and then placed on the surface of the hole transport layer for film formation.
[0185] The specific content is as follows: Cs with a molar concentration of 1.7 mol / L 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 After the perovskite precursor solution of 3 was placed for 20 days, it was placed on the surface of the hole transport layer for film formation; a perovskite thin film was formed, and a perovskite layer with a thickness of 600 nm was formed by annealing.
[0186] The perovskite precursor solution uses a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), with a volume ratio of 4:1.
[0187] Performance testing The perovskite solar cells provided in Examples 1-24 and Comparative Examples 1-4 of this application were tested under standard test conditions to obtain the open-circuit voltage Voc, fill factor FF, short-circuit current density Jsc, and photoelectric conversion efficiency PCE of the perovskite solar cells. The test results are shown in Table 1.
[0188] The fill factor (FF) used in this paper refers to the ratio of the actual maximum obtainable power (Pm or Vmp × Jmp) to the theoretical (not actually obtainable) power (Jsc × Voc). Therefore, FF can be determined by the following formula: FF = (Vmp × Jmp) / (Jsc × Voc), Where Jmp and Vmp represent the current density and voltage at the maximum power point (Pm), respectively, which is obtained by changing the resistance in the circuit until J×V reaches its maximum value; Jsc and Voc represent the short-circuit current and open-circuit voltage, respectively. The fill factor is a key parameter for evaluating perovskite solar cells. Commercial perovskite solar cells typically have a fill factor of approximately 60% or higher.
[0189] The open-circuit voltage (Voc) used in this paper is the potential difference between the anode and cathode of the device under conditions of no external load connection.
[0190] The short-circuit current (Isc) used in this article is the maximum current flowing through the output terminal of a photovoltaic cell or module when it is short-circuited (voltage V=0) under STC conditions.
[0191] The power conversion efficiency (PCE) of perovskite solar cells used in this article refers to the percentage of power converted from absorbed light into electrical energy, expressed as a percentage (%). The PCE of perovskite solar cells can be measured under standard test conditions (STC) with incident light irradiance (E: W / m²). 2 ) and the surface area (Ac:m) of perovskite solar cells 2The STC is calculated by dividing by the point of maximum power (Pm). STC typically refers to the value at a temperature of 25°C and an irradiance of 100 W / m². 2 The spectrum of air quality 1.5 (AM1.5).
[0192] Table 1 provides test data for the perovskite solar cells provided in Examples 1-24 and Comparative Examples 1-4.
[0193] Table 1
[0194] As shown in Table 1 above, the photoelectric conversion efficiency (PCE) of perovskite solar cells prepared by placing perovskite precursor solution a for 20 days in experiments 1-6 is better than that of perovskite solar cells prepared by placing perovskite precursor solution a for 20 days in the control group.
[0195] The comparative experiments showed that without adding a stabilizer to the perovskite precursor solution, the perovskite solar cells prepared in Comparative Examples 1-4 after being left to stand for 1, 5, 10, and 20 days decreased the photoelectric conversion efficiency (PCE) of the perovskite solar cells from 29.3% to 23.77%. Furthermore, the degradation rate of the PCE of the perovskite solar cells increased with the length of time the perovskite precursor solution remained at that level, reaching 18.9% (greater than 10%). This demonstrates that aging of the perovskite precursor solution reduces the PCE of perovskite solar cells.
[0196] The first set of experiments showed that adding 3-mercaptopropionic acid (2 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing the perovskite solar cells of Examples 1-4, maintained the photoelectric conversion efficiency (PCE) of the perovskite solar cells within the range of 30%-31%. As the placement time of perovskite precursor solution a increased, the degradation rate of the PCE of the obtained perovskite solar cells was low. The PCE degradation rate of the solar cell provided in Example 4 compared to Example 1 was approximately 2.1% (less than 10%), and the short-circuit current showed no degradation throughout the process. This indicates that adding 3-mercaptopropionic acid to the perovskite precursor solution can inhibit the aging of the perovskite precursor solution and maintain the PCE of the perovskite solar cells.
[0197] The second set of experiments showed that adding 3-mercaptopropionic acid (1 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing the perovskite solar cells of Examples 5-8, maintained the photoelectric conversion efficiency (PCE) of the perovskite solar cells within the range of 28.9%-30%. With the increase in the placement time of perovskite precursor solution a, the degradation rate of the PCE of the obtained perovskite solar cells was relatively low. The PCE degradation rate of the solar cell provided in Example 8 compared to Example 5 was approximately 3.5% (less than 10%). This demonstrates that adding 3-mercaptopropionic acid to the perovskite precursor solution can inhibit the aging of the perovskite precursor solution and maintain the PCE of the perovskite solar cells.
[0198] The third set of experiments showed that adding 4-mercaptobutyric acid (2 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing the perovskite solar cells of Examples 9-12, maintained the photoelectric conversion efficiency (PCE) of the perovskite solar cells within the range of 27.6%-30%. With the increase in the placement time of perovskite precursor solution a, the degradation rate of the PCE of the obtained perovskite solar cells was relatively low. The PCE degradation rate of the solar cell provided in Example 12 was approximately 6.5% (less than 10%) compared to that provided in Example 9. This demonstrates that adding 4-mercaptobutyric acid to the perovskite precursor solution can inhibit the aging of the perovskite precursor solution and maintain the photoelectric conversion efficiency of the perovskite solar cells.
[0199] The fourth set of experiments showed that adding 3-mercaptopropionic acid (3 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing the perovskite solar cells of Examples 13-16, maintained the photoelectric conversion efficiency (PCE) of the perovskite solar cells within the range of 25.97%-28.78%. With the increase in the placement time of perovskite precursor solution a, the degradation rate of the PCE of the obtained perovskite solar cells was relatively low. The PCE degradation rate of the solar cell provided in Example 16 compared to Example 13 was approximately 9.7% (less than 10%). This demonstrates that adding 3-mercaptopropionic acid to the perovskite precursor solution can inhibit the aging of the perovskite precursor solution and maintain the PCE of the perovskite solar cells.
[0200] The fifth set of experiments shows that adding 3-mercaptopropionic acid (0.5 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing perovskite solar cells of Examples 17-20, resulted in perovskite solar cells with a power conversion efficiency (PCE) in the range of 26.29%-29.93%. The PCE degradation rate of the solar cell provided in Example 20 compared to Example 17 was approximately 12.16% (greater than 10%). This indicates that when the mass-volume concentration of the stabilizer (3-mercaptopropionic acid) in the perovskite precursor solution is less than 1 mg / mL, it cannot effectively prevent the performance degradation of the perovskite layer caused by the aging of the perovskite precursor solution, thereby reducing the PCE of the perovskite solar cell.
[0201] The sixth set of experiments showed that adding 3-mercaptopropionic acid (4 mg / mL) to the perovskite precursor solution to form perovskite precursor solution a, and then placing perovskite precursor solution a for 1 day, 5 days, 10 days, and 20 days before preparing the perovskite solar cells of Examples 21-24, resulted in a power conversion efficiency (PCE) of perovskite solar cells in the range of 24.51%-28.25%. The PCE degradation rate of the solar cell provided in Example 24 compared to Example 21 was approximately 13.23% (greater than 10%). This indicates that when the mass-volume concentration of the stabilizer (3-mercaptopropionic acid) in the perovskite precursor solution is 4 mg / mL, the stabilizer will aggregate, failing to effectively inhibit the deprotonation side reaction of organic cations in the perovskite precursor solution, and failing to effectively improve the stability of the perovskite precursor solution, thereby reducing the PCE of the perovskite solar cell.
[0202] This application embodiment can also provide a photovoltaic module (not shown), which includes the perovskite solar cell described above. The perovskite solar cell can be connected in series and / or in parallel with one or more other solar cells in a predetermined manner. Multiple cells can form a cell string, and adjacent cells can be connected together by string welding.
[0203] It should be noted that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. The directional terms "inner" and "outer" refer to the inside or outside relative to the outline of the component itself. For example, if a device in the drawings is inverted, a device described as "above" or "on top of" other devices or structures will subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used herein are interpreted accordingly.
[0204] It should also be noted that, in this application, the terms "one embodiment," "another embodiment," or "embodiment," etc., refer to specific features, structures, or characteristics described in connection with that embodiment, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0205] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0206] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of patent protection of this application. Any equivalent structural or procedural changes made using the content of this application’s specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of this application.
Claims
1. A stabilizer, characterized in that, The stabilizer includes compounds with the general formula ARB; Wherein, R includes an alkyl carbon chain; A includes at least one of thioether group, mercapto group, and thiocarboxyl group; and B includes at least one of sulfonic acid group, carboxyl group, and carbamate group. The stabilizer is used in the perovskite layer, the alkyl carbon chain includes a C2-C6 carbon chain, and A and B are bonded through R to form a structure capable of reacting with Pb²⁺. + Coordination chelate ring.
2. The stabilizer according to claim 1, characterized in that, The stabilizer includes at least one of 3-mercaptopropionic acid, 4-mercaptobutyric acid, 5-mercaptovalerate, or 6-mercaptohexanoic acid.
3. A perovskite precursor solution, characterized in that, Includes the stabilizer as described in claim 1.
4. A perovskite layer comprising the stabilizer according to any one of claims 1-2 or prepared from the perovskite precursor solution according to claim 3.
5. A perovskite solar cell, characterized in that, It includes a first carrier functional layer, the perovskite layer as described in claim 4, and a second carrier functional layer, which are stacked sequentially.
6. The perovskite solar cell according to claim 5, characterized in that, The first carrier functional layer and the second carrier functional layer are each independently selected from either the hole transport layer or the electron transport layer, and the first carrier functional layer and the second carrier functional layer are different.
7. The perovskite solar cell according to claim 5, characterized in that, The thickness of the perovskite layer is 400nm-800nm.
8. A perovskite tandem solar cell, characterized in that, The perovskite tandem solar cell comprises a silicon base cell and the perovskite solar cell as described in claim 5, which are stacked sequentially.
9. A method for fabricating a perovskite solar cell, characterized in that, Includes the following steps: A first carrier functional layer is formed on a conductive substrate; The perovskite precursor solution as described in claim 3 is applied to the surface of the first carrier functional layer to form a perovskite thin film, which is then annealed to form a perovskite layer. A second carrier functional layer is formed on the perovskite layer; A transparent conductive layer is formed on the second carrier functional layer.
10. The method for preparing a perovskite solar cell according to claim 9, characterized in that, The mass-volume concentration of the stabilizer in the perovskite precursor solution is 1 mg / mL to 3 mg / mL.
11. A photovoltaic module, characterized in that, This includes solar cells as described in any one of claims 5-8 or solar cells prepared by the method described in claim 9 or 10.
Citation Information
Patent Citations
Stable perovskite precursor solution and preparation method and application thereof
CN119855467A